2017
DOI: 10.1038/srep44819
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial effects of paeoniflorin on non-alcoholic fatty liver disease induced by high-fat diet in rats

Abstract: Non-alcoholic fatty liver disease (NAFLD) is the most prevalent form of chronic liver diseases. This study sought to evaluate the insulin-sensitizing effect of paeoniflorin (PF) on high-fat diet-induced NAFLD and possible molecular mechanisms. Male Sprague Dawley rats were fed a high-fat diet (HFD) for 10 weeks to establish the NAFLD model, and PF (20 mg/kg/d) was gavaged to the NAFLD rats for another four weeks. Our results demonstrated that HFD resulted in hepatocellular ballooning, micro-/macrovesicular ste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
51
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(61 citation statements)
references
References 30 publications
9
51
0
1
Order By: Relevance
“…Histopathology in this study showed that HFD displayed characteristic features of nonalcoholic steatohepatitis (NASH). These results were in agreement with results of Ma et al [27] Oral administrations of C. olitorius extract (300 or 400 mg/mg/kg) or orlistat reduced hepatic fat accumulation, alleviated swelling of hepatocytes and prevented the formation of steatosis. The C. olitorius extract was significantly more effective in comparison with orlistat and displayed at the nearly normal appearance compared to the ND control group.…”
Section: Discussionsupporting
confidence: 93%
“…Histopathology in this study showed that HFD displayed characteristic features of nonalcoholic steatohepatitis (NASH). These results were in agreement with results of Ma et al [27] Oral administrations of C. olitorius extract (300 or 400 mg/mg/kg) or orlistat reduced hepatic fat accumulation, alleviated swelling of hepatocytes and prevented the formation of steatosis. The C. olitorius extract was significantly more effective in comparison with orlistat and displayed at the nearly normal appearance compared to the ND control group.…”
Section: Discussionsupporting
confidence: 93%
“…From each rat, a skeletal muscle sample (100-150 g) was obtained and homogenized in phosphate buffer (pH 7.0) at 4 ∘ C with a homogenizer (UP100H, Hielscher Ultrasonics, Berlin, Germany). The homogenized tissue was centrifuged at 12000 rpm at 4 ∘ C for 15 min [19], and the supernatant was collected for gene expression analysis. Additionally, a blood sample was collected from the abdominal aorta for measurement of the blood insulin and glucose levels.…”
Section: Sample Collection and Measurementsmentioning
confidence: 99%
“…A study demonstrated that Rg1 and Rb1 were involved improving lipid levels and ameliorate in ammation in NAFLD mice [28]. Paeoni orin has obvious effects on suppressing lipid ectopic deposition, enhancing insulin sensitivities and decreasing oxidation in NAFLD rats [29,30]. Astragaloside has obvious anti-lipid accumulation effects through regulating AMPK signal in NAFLD cell models [31,32].…”
Section: Discussionmentioning
confidence: 99%